Nonbook materials : the organization of integrated collections - Weihs, Jean.; Lewis, Shirley; Macdonald, Janet; Joint Advisory Committee on Nonbook Materials (Ottawa : Canadian Library Association, 1973)
This book has been written for all types of libraries and media centres which wish to have an omnimedia catalogue, i.e., one in which the entries for all materials, both book and nonbook, are interfiled. Nonbook Materials has developed its rules according to the precepts of Parts I and II of the Anglo-American Cataloging Rules, varying these rules only when the nature of the material demands it.
In consultation with the CLA/ALA/AECT/EMAC/CAML Advisory Committee on the Cataloguing of Nonbook Materials.
Includes index.
Includes bibliographical references: p. 101-104.
aia 16/06/2017
Loans
Keywords: Cataloging of nonbook materials